2000
DOI: 10.1007/bf02344875
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renormalised entropy for risk stratification using heart rate variability data

Abstract: Standard time and frequency parameters of heart rate variability (HRV) describe only linear and periodic behaviour, whereas more complex relationships cannot be recognised. A method that may be capable of assessing more complex properties is the non-linear measure of 'renormalised entropy.' A new concept of the method, RE(AR), has been developed, based on a non-linear renormalisation of autoregressive spectral distributions. To test the hypothesis that renormalised entropy may improve the result of high-risk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…HRV measurements have proven to be independent predictors of sudden cardiac death after acute myocardial infarction, chronic heart failure or dilated cardiomyopathy [17,21,27,33,34,38]. Moreover, it has been shown that shortterm HRV analysis already has an independent prognostic value in risk stratification apart from that of clinical and functional variables [23].…”
Section: Introductionmentioning
confidence: 98%
“…HRV measurements have proven to be independent predictors of sudden cardiac death after acute myocardial infarction, chronic heart failure or dilated cardiomyopathy [17,21,27,33,34,38]. Moreover, it has been shown that shortterm HRV analysis already has an independent prognostic value in risk stratification apart from that of clinical and functional variables [23].…”
Section: Introductionmentioning
confidence: 98%
“…In addition to their primary clinical role to reduce the incidence of sudden cardiac death, data that were recorded in ICDs and subsequently downloaded have also been used to analyze the conditions that precede the onset of VT and VF [5, 8-11, 20, 25, 28, 30, 31, 34, 37, 39, 43, 46]. The data derived from ICDs complement data from other sources that have analyzed heart rate variability (HRV) [8,17,19,28,36,48,49,51], premature ventricular complexes (PVCs) [1,4,7,15,26,40,41,44], and T-wave alternans [18,23,35,38] in assessment of factors that lead to the initiation of ventricular tachycardia and confer an increased risk for sudden cardiac death. Many factors including increased heart rate [16,19,20,24,27,31,34], reduced HRV [11,17,19,22,28,30,31,36,43,45,48,49], increased incidence of PVCs [4,7,16,40,44], and T-wave alterna...…”
Section: Introductionmentioning
confidence: 99%
“…Considering the later one takes account of the relationship between neighboring points, hence it is more conducive to find property of signals. In the symbolizing process, the range between the maximum and minimum values was divided into 2 or 4 intervals [23][24][25].…”
Section: Symbolic Intrinsic Mode Functionmentioning
confidence: 99%